Production of Ipomoea Batatas (L.) Lam in an Agroforestry System in Santarem, Pará¡ Preliminary Results (Boletim de Indústria Animal, 2022)
Agroforestry systems (AFSs) are defined as areas with mixed production of trees and crops, including forage for livestock. The objective is to maintain production in a sustainable way. In this study, we evaluated the production of sweet potato in different agroforestry arrangements. This tuber was chosen because it has a short cycle, ranging from 90 to 120 days, and has good market acceptance. The experiment was carried out at the experimental farm of the Universidade Federal do Oeste do Pará (UFOPA), located in the municipality of Santarém, in the western region of Pará state. The soil of the experimental area is classified as an ardissolic dystrophic yellow latosol, with levels of sand between 439 and 679g/kg, silica from 64 to 99g/kg and clay between 234 and 479g/kg. The experimental design adopted was a completely randomized, consisting of 3 plots (1x5m) in each treatment. The planting areas had been submitted to two reforestation practices and a control with cultivation in full sun. The shaded areas chosen for the experiment were planted with teak (Tectona grandis) and African mahogany (khaya sp), both with 3x2m spacing, with 5 years of age. After choosing the planting space, measurements were made of the plots that had similar sizes in the three treatments: full sun, teak and African mahogany. For planting, windrows were established in the form of a mound higher than the surrounding ground, approximately 30 cm high. The tuberous roots of sweet potatoes were planted and were harvested after 138 days, when the potatoes reached physiological maturity. After harvesting, the material was taken to the UFOPA forest seed laboratory, where all morphometric analysis procedures were performed. Results showed that the treatment in full sun was superior to the shaded treatments (Teak and African Mahogany). In full sun, 90 potatoes were produced, in Teca 13 potatoes were produced and in mahogany 19 potatoes. These results show that sweet potato is not well adapted to shaded areas.